Practical synthesis of pharmaceutically relevant molecules enriched in sp3 character. Issue 1 (30th November 2017) - Campbell, Peter S.; Jamieson, Craig; Simpson, Iain; Watson, Allan J. B.
Abstract : A highly efficient and general procedure for the preparation of medicinally relevant compounds with enhanced 3D character is reported. Abstract : The expedient synthesis of compounds enriched in sp 3 character is key goal in modern drug discovery. Herein, we report how a single pot Suzuki–Miyaura-hydrogenation can be used to furnish lead and fragment-like products in good to excellent yields. The approach has been successfully applied in formats amenable to parallel synthesis, in an asymmetric sense, and in the preparation of molecules with annotated biological activity.